Mitos clásicos en la Gemäldegalerie Alte Meister de Kassel - Blázquez, José María (Anales de Historia del Arte, 2007)
This article studies the Classic myths represented in the pictures of the Gemäldegalerie Alte Meister de Kassel, observing their influence through the Italian authors from the Renaissance. The use of myths serves at the diverse artists to shape the restlessness of its time.